Proposing the Appropriate Teaching Methods under Scientific Approach of Curriculum 2013 (K-13) for Teaching English for Junior High School in Indonesia - Ibrahim, Rokib Nur (Journal of English Teaching, Literature, and Applied Linguistics, 2018)
Teaching English as foreign language is the term, which is used by teacher where English is not used in the learners’ daily life. The English is only used in some places, which English as the official or instruction language, in the office and school for instance. Therefore, in teaching this language, teacher needs some strategies and methodologies, to rise up either students’ motivation or willingness, so that the goal of learning can be achieved. Accordingly, the Ministry of Education and Culture of Indonesia has released a new curriculum along with its approach, three methodologies and five strategies, which those must be applied in every teaching and learning process. On the other hand, there are many strategies in language teaching offered by the experts, which can be mixed by teacher in one meeting, like summarizing and note taking, create, and memory strategies for instance. Besides, the three methodologies, which are Project-Based, Problem-Based, and Discovery learning, are hard to choose by English teacher, which is caused by the traditional teaching habit of teacher and their lack of knowledge about those three methodologies before. Therefore, this article discusses about to propose the appropriate of methodologies and strategies used under the Scientific Approach, so that teachers are able to know which method that is appropriate for their class activity.